Environmental Stressors on Skin Aging. Mechanistic Insights - Parrado, Concepcion; Mercado-Saenz, Sivia; Perez-Davo, Azahara; Gilaberte, Yolanda; Gonzalez, Salvador; Juarranz, Angeles (Frontiers in Pharmacology, 2019)
The skin is the main barrier that protects us against environmental stressors (physical, chemical and biological). These stressors, combined with internal factors, are responsible for cutaneous aging throughout life. Furthermore, they also negatively impact the skin and represent an increased risk of skin diseases, particularly skin cancer. This review addresses the impact of environmental stressors on skin aging, especially those related to general and specific external factors (lifestyles, occupations, pollutants and light exposure). More specifically, we have evaluated ambient air pollution, household air pollutants from non-combustion sources, and exposure to light (UV radiation, blue and red light). We approach the molecular pathways involved in skin aging and pathology, as a result of exposure to these external environmental stressors. Finally, we make a reflection of how several components of environmental stress can interact with ultraviolet radiation to cause cell damage and the critical importance of knowing the mechanisms to develop new therapies to maintain the skin without damage in old age and to repair the diseases of the skin.